Drugs used to treat joint and muscle disease. Issue 1 (January 2021) - de Gray, Lorraine E.; Seth, Bharti
Abstract: Musculoskeletal disorders have a very diverse aetiology. They have a significant impact on each individual sufferer's quality of life and society as a whole. The last three decades have seen revolutionary changes in the management of autoimmune-related muscle and joint disorders due to the introduction of biologics. Management of spasticity disorders remain challenging, although implantable technology has broadened mode of delivery.